The correspondence of Gregorio Bermann to Deodoro Roca - Vera de Flachs, Maria Cristina (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2018)
The aim of this article and its relevance lies in giving to know some private letters, unknown until today, sent to Deodoro Roca by Dr. Gregorio Bermann, a reformist intellectual. To study the correspondence, we used the content analysis that allows to discover the DNA of the messages and reconstructs their architecture, structure, and reveals the basic components. In summary, the analyzed correspondence confirms the friendship between Bermann and Roca throughout their lives, their concerns about the university and the problems of the generation of 1918.